Structural elucidation of three antioxidative polysaccharides from Tricholoma lobayense. (10th February 2017) - Chen, Yan; Li, Xue-Hui; Zhou, Li-Yuan; Li, Wan; Liu, Liu; Wang, Dan-Dan; Zhang, Wen-Na; Hussain, Sajid; Tian, Xiao-He; Lu, Yong-Ming
Graphical abstract: Highlights: Three polysaccharides from Tricholoma lobayense were characterized. TLH-1 and TLH-2 are glucans with medium molecular weights. TLH-3 is a novel glucogalactan with low molecular weight. Due to the structural complexity, TLH-3 exhibits excellent antioxidant activity. TLH-3 shows great advantages as a new antioxidant agent. Abstract: Tricholoma lobayense is a nutritious mushroom with great health benefits. Three polysaccharides with purity higher than 99% were successfully extracted from Tricholoma lobayense . The molecular weights of TLH-1, TLH-2 and TLH-3 were determined to be 8.43 × 10 5 ，5.36 × 10 5 and 4.53 × 10 3  Da, respectively. The backbones of TLH-1 and TLH-2 were mainly composed of 1, 4-linked α-d -glucopyranosyl. However, polysaccharide TLH-3 was found to be a highly branched glucogalactan, which is made up of 1, 3-linked α-d -glucopyranosyl branched at C-6 and 1, 3-linked β -d -galactopyranosyl. In vitro antioxidant activity assays revealed that TLH-3 exhibited highest antioxidant activities among the polysaccharides from Tricholoma lobayense, which were comparable to those of ascorbic acid. The results suggested that the outstanding antioxidant activities of TLH-3 might depend on its low molecular weight, high branch degree, versatile linkage types and complex conformation. These characteristics make TLH-3 an attractive natural antioxidant for food and pharmaceutical applications.